Eutrophic levels and algae growth increase emissions of methane and volatile sulfur compounds from lakes. (1st August 2022) - Wang, Jing; Wei, Zhi-Peng; Chu, Yi-Xuan; Tian, Guangming; He, Ruo
Abstract: Eutrophic lakes are hot spots of CH4 and volatile sulfur compound (VSC) emissions, especially during algal blooms and decay. However, the response of CH4 and VSC emissions to lake eutrophication and algae growth as well as the underlying mechanisms remain unclear. In this study, the emissions of CH4 and VSCs from four regions of Lake Taihu with different eutrophic levels were investigated in four months (i.e., March, May, August and December). The CH4 emissions ranged from 20.4 to 126.9 mg m −2 d −1 in the investigated sites and increased with eutrophic levels and temperature. H2 S and CS2 were the dominant volatile sulfur compounds (VSCs) emitted from the lake. The CH4 oxidation potential of water ranged from 2.1 to 14.9 μg h −1 L −1, which had positive correlations with trophic level index and the environmental variables except for the NH4 + -N concentration. Eutrophic levels could increase the abundances of bacteria and methanotrophs in lake water. α- Proteobacteria methanotroph Methylocystis was more abundant than γ- Proteobacteria methanotrophs in March and May, while the latter was more abundant in August and November. The relative abundance of Cyanobacteria, including Microcystis, A . granulata var. angustissima and Cyanobium had significantly positive correlations with temperature, turbidity, SO4 2- -S, and total sulfur. Partial least squares path modelling revealed that the algal growth could promote VSC emissions, which had a positive correlation with CH4 oxidation potential, likely due to the positive correlation between the CH4 and VSC emissions from lakes. These findings indicate that water eutrophication and algae growth could increase the emissions of CH4 and VSCs from lakes. Controlling algae growth might be an effective way to mitigate the emissions of CH4 and VSCs from freshwater lakes. Graphical abstract: Image 1 Highlights: CH4 emissions increased with lake eutrophic levels and temperature in Lake Taihu. H2 S and CS2 were the dominant volatile sulfur compounds emitted from the lake. CH4 oxidation potential had a positive correlation with trophic level index. γ- Proteobacteria methanotrophs dominate in water during algae blooms and decay. Algal growth could promote VSCs emissions.